Youth and popular culture in Africa : media, music, and politics - Ugor, Paul (Rochester studies in African history and the diaspora, 2021)
"The edited collection focuses on the links between young people and African popular culture. It explores popular culture produced and consumed by young people in contemporary Africa. And by "culture," we mean all kinds of texts or representations-visual, oral, written, performative, fictional, social, and virtual-created by African youth, mostly about their lives and their immediate societies, and for themselves, but also consumed by the larger public, and shared locally and globally. We proceed from the premise that cultural texts not only function as "social facts" as Karin Barber argues, but that they double as "commentaries upon, and interpretations of, social facts. They are part of social reality, but they also take up an attitude to social reality" (2007, 04). So, the work focuses specifically on what African youth produce as popular culture, under what conditions or contexts they produce such work, how they produce those texts, why they produce them, the aesthetic dimensions of these texts as cultural artifacts, and why these textual practices matter as social facts, as interpretive acts, and as cultural symbols of the general cultural activism of young people in a rapidly changing world, a world where the global cultural economy is the prime terrain for the relentless struggles over the meanings that come to shape political-economic and social systems"--